Analysis and design of an unequal termination impedance power divider with bandpass filtering response. Issue 18 (14th August 2017) - Kim, P.; Chaudhary, G.; Jeong, Y.
Abstract : The design of an unequal termination power divider (PD) with a bandpass filtering response and wide out‐of‐band suppression characteristics is presented. The two‐cascaded coupled lines can be designed with a low impedance transforming ratio. For the validation, a 50‐to‐5 Ω termination impedance PD was implemented at a centre frequency ( f 0 ) of 2.6 GHz. The measured results are in good agreement with the simulations, showing input and output return losses that are better than 19 dB over a passband bandwidth of 190 MHz (2.51–2.7 GHz), and an out‐of‐band suppression that is better than 19.6 dB from DC to 2.25 and 2.9 to 7.2 GHz. The isolation between the output ports is 39.2 dB at f 0, and it is better than 19 dB with a broadband frequency (DC to 7.2 GHz).